Analisis dan usulan perbaikan risiko kecelakaan kerja dengan metode HIRARC (Hazard Identification Risk Assesment And Risk Control) di PT Putra Jawamas - Bagus , Alfin Rizki; Saifuddin, Joumil Aidil (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Occupational Safety and Health (K3) is an aspect that must be prioritized by all companies to protect employees from the risk of work accidents. PT Putra Jawamas is engaged in the repair and fabrication sector which has activities that can trigger work accidents. HIRARC is the right step to be implemented in companies to identify, analyze, and reduce K3 risks that can occur in the work environment. The purpose of this study was to examine the level of K3 risk with a risk assessment method using a risk assessment matrix on work activities carried out at PT Putra Jawamas. The results of the study showed that the work carried out had several different levels of risk, the most extreme level being the welding process which can cause burns. The control efforts that can be made are maintaining quality and using welding equipment according to SOP and using personal protective equipment.